Overnutrition in Infants Is Associated With High Level of Leptin, Viral Coinfection and Increased Severity of Respiratory Infections: A Cross-Sectional Study - Arias-Bravo, Guisselle; Valderrama, Gustavo; Inostroza, Jaime; Reyes-Farías, Marjorie; Garcia-Diaz, Diego F.; Zorondo-Rodríguez, Francisco; Fuenzalida, Loreto F. (Frontiers in Pediatrics, 2020)
Objective: To investigate the relationship of overnutrition (obese and overweight) with severity of illness in children hospitalized with acute lower respiratory infections (ALRIs), frequency of viral coinfections and leptin levels. Methods: We studied 124 children less than 2 years old that were hospitalized for ALRI. Nutritional status was calculated by z-scores according to weight-for-age z-scores, length or height-for-age z-scores, and weight-for-height z-scores. Nasopharyngeal aspirates (NPAs) were obtained and viral respiratory pathogens were identified using reverse transcription polymerase chain reactions (RT-PCR). Respiratory syncytial virus (RSV) load was assessed using quantitative RT-PCR. NPA and plasma leptin level were measured. Clinical data and nutritional status were recorded, and patients were followed up until hospital discharge. Viral coinfection was defined as the presence of two or more viruses detected in the same respiratory sample. Severity of illness was determined by length of hospitalization and duration of oxygen therapy. Results: children with overnutrition showed a greater frequency of viral coinfection than those with normal weight (71% obese vs 37% normal weight p = 0.013; 68% overweight vs 37% normal weight p = 0.004). A lower RSV load was found in obese (5.91 log10 copies/mL) and overweight children (6.49 log10 copies/mL) compared to normal weight children (8.06 log10 copies/mL; p = 0.021 in both cases). In multivariate analysis, obese and overweight infants less than 6 months old were associated with longer hospital stays (RR= 1.68; CI: 1.30 – 2.15 and obese: RR= 1.68; CI: 1.01 – 2.71, respectively) as well as a greater duration of oxygen therapy (RR= 1.80; IC: 1.41 – 2.29 and obese: RR= 1.91; CI: 1.15 – 3.15, respectively). Obese children less than 6 months showed higher plasma leptin level than normal weight children (5.26 ng/ul vs 1.29 ng/ul; p <0.0001). Conclusions: In infants younger than 6 months, overnutrition condition was related to increased severity of infections and high plasma leptin level. Also, children with overnutrition showed a greater frequency of viral coinfection and low RSV viral load compared to normal weights children. These findings further contribute to the already existent evidence supporting the importance of overnutrition prevention in pediatric populations.